Evaluating football clubs using ORESTE and AGREPREF - Veronika Krause (Acta Universitatis Carolinae: Kinanthropologica)
In already published research, we observe that continuous multi-criteria decision-making models are often used to evaluate professional football clubs. However, some publications suggest that discrete models can also be applied. The aims of this study are to assess English Premier League clubs using two discrete multi-criteria evaluation methods and to compare their results. The chosen methods were ORESTE, which is based on an ordinal comparison of criteria and alternatives, and AGREPREF, which relies on pairwise comparisons. Six criteria were selected to represent the sporting, economic, and social objectives of the clubs. Both methods produced only a quasi-arrangement of clubs. The AGREPREF method provided a ranking more closely aligned with the clubs' final league positions. However, the final ranking is significantly influenced by the selection of criteria and the weights assigned to them. Both methods highlighted the performances of Wolverhampton Wanderers and Watford.